Nicotinamide phosphoribosyl-transferase/visfatin: a missing link between overweight/obesity and postmenopausal breast cancer? Potential preventive and therapeutic perspectives and challenges. - Dalamaga, Maria (Med Hypotheses, 2012)
Worldwide breast cancer (BC) constitutes a significant public health concern. Excess body weight is associated with postmenopausal BC (PBC) risk. Recent studies have shown that the constellation of obesity, insulin resistance and serum adipokine levels are associated with the risk and prognosis of PBC. Nicotinamide phosphoribosyl-transferase (Nampt), also known as visfatin and pre-B-cell-colony-enhancing factor, found in the visceral fat, represents a novel pleiotropic adipokine acting as a cytokine, a growth factor and an enzyme. It plays an important role in a variety of metabolic and stress responses as well as in the cellular energy metabolism, particularly NAD biosynthesis. Nampt exhibits proliferative, anti-apoptotic, pro-inflammatory and pro-angiogenic properties. Nampt's insulin-mimetic function remains a controversial issue. Circulating Nampt levels are increased in obese women. Also, Nampt levels are significantly elevated in women suffering from PBC than in healthy controls independently from known risk factors of BC, anthropometric and metabolic parameters as well as serum concentrations of well known adipokines. High expression of Nampt in BC tissues was reported to be associated with more malignant cancer behavior as well as adverse prognosis. Taking into account the mitogenicity of Nampt as well as its proliferative, anti-apoptotic and pro-angiogenic properties, a novel hypothesis is proposed whereas Nampt may be involved in the etiopathogenesis of PBC and may represent a missing link between overweight/obesity and PBC. Nampt could exert its effects on the normal and neoplastic mammary tissue by endocrine and paracrine mechanisms; Nampt could also be secreted by tumor epithelial cells in an autocrine manner. It could stimulate mammary epithelial cell proliferation, invasion, metastasis, and angiogenesis, which is essential for BC development and progression. Serum Nampt might be a novel risk factor as well as a potential diagnostic and prognostic biomarker in PBC. In addition, pharmacologic agents that neutralize biochemically Nampt or medications that decrease Nampt levels or downregulate signaling pathways downstream of Nampt may prove to be useful anti-cancer agents. The potential harmful effect on PBC risk due to vitamin B3 (nicotinic acid, a natural NAD precursor in the biosynthetic route leading to NAD) intake is speculated for the first time. In this hypothesis, the role of Nampt in BC carcinogenesis and progression is explored as well as the pathophysiological mechanisms that underlie the association between Nampt and PBC in the context of a dysfunctional adipose tissue in obesity. Understanding of these mechanisms may be important for the development of preventive and therapeutic strategies against PBC.
Keywords: Breast Neoplasms; Cytokines; Female; Humans; Nicotinamide Phosphoribosyltransferase; Obesity; Overweight; POSTMENOPAUSE